Sunset park - Auster, Paul. (New York : Picador, 2011)
After falling in love with an underage girl and stirring the wrath of her older sister, New York native Miles Heller flees to Brooklyn and shacks up with a group of artists squatting in the borough's Sunset Park neighborhood.
Keywords: Young adults -- Fiction